EVALUASI EROSI PADA BERBAGAI PENGGUNAAN LAHAN DI DAS TAWAELI KECAMATAN PALU UTARA, KOTA PALU - Wardana, Suci; Ramlan, Ramlan; Rahman, Abdul (AGROTEKBIS, 2017)
This study aims to determine the index of erosion in different land uses in the watershed Tawaeli North Palu subdistrict, Palu. The usefulness of this research is as a source of information for the various parties in relation to land resources management policy, It is also expected to be useful as reference data for further research. The research was conducted from October to December 2015, held in DAS Tawaeli, North Palu subdistrict, Palu and Laboratory of Soil Science, Faculty of Agriculture, University Tadulako. These results indicate At shrub land and cacao plantations have erosion hazard index values are relatively low (<1) so no need for soil conservation measures. Erosion hazard index value (> 1) and is classified clove plantations are on land, in value of 1.52, 1.83 and 1.94. An erosion hazard index value greater than 1 is necessary to soil conservation measures such as contour planting, terracing, and the selection of appropriate plant cover.Â Key Words : Erosion hazard index, Plantation Cocoa and Plantation Cloves, shrublands.